2015
DOI: 10.1111/jvec.12165
|View full text |Cite
|
Sign up to set email alerts
|

Determining meteorological drivers of salt marsh mosquito peaks in tropical northern Australia

Abstract: In northern Australia the northern salt marsh mosquito Aedes vigilax is a vector of Ross River virus and is an appreciable pest. A coastal wetland adjacent to Darwin's residential suburbs offers a favorable habitat for Ae. vigilax, and despite vigilant mosquito control efforts, peaks of Ae. vigilax occur in excess of 500/trap/night some months. To improve mosquito control for disease and nuisance biting to nearby residential areas, we sought to investigate meteorological drivers associated with these Ae. vigil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Moisture is an essential component in saltmarsh mosquito egg conditioning Baker 1962, Kay andJorgensen 1986) and hatching (Andreadis 1990, Rydzanicz et al 2011, Cardo et al 2012) and many studies correlate Aedes spp. with wet, lower regions of saltmarshes that are periodically flooded by tide (De Little et al 2009, Jacups et al 2009, Cardo et al 2012. We found that soil moisture was greatest in bare soil and runnel habitat than shrubby glasswort and samphire, but there was no relationship between soil moisture and elevation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moisture is an essential component in saltmarsh mosquito egg conditioning Baker 1962, Kay andJorgensen 1986) and hatching (Andreadis 1990, Rydzanicz et al 2011, Cardo et al 2012) and many studies correlate Aedes spp. with wet, lower regions of saltmarshes that are periodically flooded by tide (De Little et al 2009, Jacups et al 2009, Cardo et al 2012. We found that soil moisture was greatest in bare soil and runnel habitat than shrubby glasswort and samphire, but there was no relationship between soil moisture and elevation.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, both soil moisture and elevation may be relevant factors contributing to egg distribution. Generally, there are strong correlations among elevation, tide height, and soil moisture within saltmarshes (Saintilan 2009b, Prahalad et al 2012, which also correspond to mosquito abundance , Jacups et al 2009). Moisture is an essential component in saltmarsh mosquito egg conditioning Baker 1962, Kay andJorgensen 1986) and hatching (Andreadis 1990, Rydzanicz et al 2011, Cardo et al 2012) and many studies correlate Aedes spp.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of mosquito-borne disease is controlled by a combination of environmental, and vector and reservoir host dynamics, which vary across geographical and climatic regions. In forecasting the transmission of RRV, previous studies have used monthly environmental data and have highlighted the importance of having mosquito trapping data to supplement environmental predictors [13,30,36]. While these studies have been vital in developing our understanding of RRV epidemics, their course temporal resolution and recruitment for labour intensive surveillance [13,24,29,[37][38][39][40][41][42] limit practical application for timely forecasts to inform mitigation activities and public awareness campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify optimum temperature ranges at which the maximum mosquito abundance occurs for each species to effectively implement vector control measures. An estimate of the nonlinear relationship between mosquito abundance and daily average temperatures, based on the lag effect that takes into account the period of 2 weeks from egg to adult before the collection date, was performed [23,24]. In subsequent years, these data can be used to determine the effectiveness of vector control measures, e.g., different type of adult fogging measures (e.g., ULV or thermal fogging) or larval control (e.g., use of Bti) to reduce disease risks.…”
Section: Discussionmentioning
confidence: 99%